2018
DOI: 10.1210/en.2018-00551
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sexual Trait Development in cyp17a1-Deficient Zebrafish

Abstract: Cytochrome P450 (Cyp)17A1 has both 17α-hydroxylase and 17,20-lyase activities, which are involved in the steroidogenic pathway that produces androgens and estrogens. Previously, a phenotype of all-male cyp17a1-deficient zebrafish generated by transcription activatorlike effector nuclease has been reported. In the current study, the mechanisms relating to Cyp17a1 that are involved in the development of sexual traits, especially gonadal differentiation and testicular development, were characterized. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 62 publications
6
80
0
Order By: Relevance
“…However, unlike other genes, cyp17a1 exhibited an entirely different expression pattern in ovary and testis and its distribution varied in different germ cells [41]. The condition of cyp17a1 hinted at the distinct roles in female and male which is agreed with the results in zebrafish [42]. These data will provide useful guideposts to distinguish different cell types; however, the specific functions of these sex-related genes in gonadal development requires further study.…”
Section: Discussionsupporting
confidence: 75%
“…However, unlike other genes, cyp17a1 exhibited an entirely different expression pattern in ovary and testis and its distribution varied in different germ cells [41]. The condition of cyp17a1 hinted at the distinct roles in female and male which is agreed with the results in zebrafish [42]. These data will provide useful guideposts to distinguish different cell types; however, the specific functions of these sex-related genes in gonadal development requires further study.…”
Section: Discussionsupporting
confidence: 75%
“…In Cyp17deficient mice, the male are infertile, and the androgen levels dropped significantly [40]. Similarly, in cyp17a1-deficient zebrafish, the androgen levels declined significantly, and their male-typical mating behaviors and secondary sex characters were compromised [41,42]. The colocalization analysis indicated that zbtb40 and cyp17a1 may have interaction during the spermatogenesis in the orange-spotted grouper.…”
Section: Discussionmentioning
confidence: 91%
“…The sexual dimorphism of cyp17a has been observed in several fish species (Chen et al, 2010;Xiong et al, 2015). In zebrafish, cyp17a1 mutants develop to all fertile males due to the decreased level of estrogen, demonstrating that cyp17a1 is essential for estrogen production and ovarian maintenance (Zhai et al, 2018).…”
Section: The Expression Change Of Sex-related Signaling Pathway Durinmentioning
confidence: 99%